THE POWER OF A STORY IN THE FUNCTION OF LANGUAGE LITERACY - Vedran Dizdarevikj (Sveučilište Josipa Jurja Strossmayera u Osijeku, Fakultet za odgojne i obrazovne, 2019)
In this paper we tried to demonstrate the power of a story in the function of language literacy. We are going to build up our argument from the general premises of the cultural psychologist Jerome Bruner dispersed in many of his books, which postulate that our experience of ourselves and the world is structured in a narrative form – like a story. We think that the best way to acquire language literacy is to start from a story and then to proceed to language. Listening to stories (told or read by a teacher) equips students with the skills and attitudes that afterwards enable easier acquisition of pre-reading and reading skills. Such pre-reading skills are making distinction between written and spoken language, recognition of articulation, intonation and diction in language, and understanding that language is always entangled in meaning. The studies have shown that having access to imaginative and properly structured stories adequate for students’ developmental level is very important and beneficial for understanding of how language works. Language and stories are essentially interconnected and one cannot exist without the other and that is why the structure of narratives discloses the structure of language.
Keywords: language, literacy, story, structure, teacher